2020
DOI: 10.1186/s12933-020-01115-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of glucose uptake of visceral fat and acute myocardial infarction: a pilot 18F-FDG PET/CT study

Abstract: Background Inflamed visceral adipose tissue (VAT) facilitates chronic inflammation in atherosclerotic lesions thereby leading to increased risk of coronary artery disease (CAD). In this study, we evaluated the glucose uptake of VAT and the carotid artery with 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET/CT) and their association with CAD, including acute myocardial infarction (AMI). Methods A total of 90 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Thus, we next examined whether VAT SUVmax showed a significant correlation with systemic inflammation in patients with endometrial cancer. As shown in Table 2 , both VAT SUVmax and V/S ratio were significantly correlated with surrogate markers for systemic inflammation, consistent with previous studies [ 23 , 24 ]. In contrast, SAT SUVmax was not significantly correlated with systemic inflammation.…”
Section: Resultssupporting
confidence: 90%
“…Thus, we next examined whether VAT SUVmax showed a significant correlation with systemic inflammation in patients with endometrial cancer. As shown in Table 2 , both VAT SUVmax and V/S ratio were significantly correlated with surrogate markers for systemic inflammation, consistent with previous studies [ 23 , 24 ]. In contrast, SAT SUVmax was not significantly correlated with systemic inflammation.…”
Section: Resultssupporting
confidence: 90%
“… 36 , 53 Pahk et al demonstrated that glucose uptake of VAT assessed by 18 F-FDG PET/CT was associated with severity of CAD and carotid artery atherosclerosis. 35 Therefore, increased VAT inflammation and metabolic activity (as demonstrated in our preliminary results) may act as a mediator for cardiovascular risk in patients with OSA.…”
Section: Discussionmentioning
confidence: 52%
“… 34 A recent study demonstrated that 18 F-FDG uptake by VAT measured using 18 F-FDG positron emission tomography (PET)/CT was positively associated with severity of coronary artery disease (CAD) and carotid artery atherosclerosis. 35 Therefore, assessing the metabolic and inflammatory properties of VAT in association with OSA is novel, and may serve as a unique imaging biomarker to quantify the inflammatory burden in VAT, potentially informing differential cardiometabolic risk profiles in subgroups of OSA patients. Hybrid 18 F-FDG PET/magnetic resonance imaging (MRI) can be utilized as a novel method for both volumetric and metabolic assessment of abdominal adipose tissue depots.…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines, secreted by adipocytes, have been receiving attention for their role in cancer metabolism 26 . Regarding VAT, a special compartment of adipocytes, its upregulated activity has been a point of focus in several studies: VAT activity was related to myocardial infarction 8 . It also reflected the inflammatory status of the carotid artery in metabolic syndrome 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%